2020
DOI: 10.1002/acm2.13041
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Comparison of the internal target volume (ITV) contours and dose calculations on 4DCT, average CBCT, and 4DCBCT imaging for lung stereotactic body radiation therapy (SBRT)

Abstract: Purpose: To investigate the differences between internal target volumes (ITVs) contoured on the simulation 4DCT and daily 4DCBCT images for lung cancer patients treated with stereotactic body radiotherapy (SBRT) and determine the dose delivered on 4D planning technique. Methods: For nine patients, 4DCBCTs were acquired before each fraction to assess tumor motion. An ITV was contoured on each phase of the 4DCBCT and a union of the 10 ITVs was used to create a composite ITV. Another ITV was drawn on the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…However, the volume of normal tissue is increased, which might increase the risk of radiation-related toxicity [4] , [5] . Dose delivery accuracy can be augmented by the use of respiratory management techniques such as abdominal compression [6] , 4-dimensional Computed Tomography (4DCT) [7] , Deep Inspiration Breath-Hold (DIBH) [8] and real-time tumor tracking [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the volume of normal tissue is increased, which might increase the risk of radiation-related toxicity [4] , [5] . Dose delivery accuracy can be augmented by the use of respiratory management techniques such as abdominal compression [6] , 4-dimensional Computed Tomography (4DCT) [7] , Deep Inspiration Breath-Hold (DIBH) [8] and real-time tumor tracking [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…After obtaining institutional ethics approval (Lawson Approval Number: R-23-086), ten (10) patients with early-stage NSCLC treated with a hypofractionated treatment scheme using a free-breathing VMAT technique were retrospectively analyzed in the treatment planning system Eclipse v15.6 (Varian Medical Systems, Palo Alto, USA). Seven patients were treated with an ablative dose defined by a BED 10 > 100 Gy, while three were retreatment scenarios with a reduced dose per fraction.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…An internal target volume (ITV) is defined as a combination of the visible tumor while considering the potential motion and deformation of the volume during treatment. Typically, an ITV is created either by taking the union of the gross tumor volume (GTV) at every respiratory phase of the patient's 4D‐CT or by directly contouring on the patient's free‐breathing CT 10 . However, widening the field size inevitably increases the amount of dose delivered to the surrounding healthy tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Dumas (2019) studied 9 patients and found that the Dice similarity coefficient (DSC) and mean center of mass (COM) is similar for avgCBCT and 4DCT. 13 Thus, we want to use a deep learning-based method to predict the ITV in CBCT and evaluate the accuracy against 4DCT delineation in this study. 4D-CBCT was not used in the current study because 4D-CBCT images also suffer from reduced image quality because of deficient projections in each phase bin after phase-sorting.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the disagreement between the external surface and actual tumor motion, especially tumors close to the diaphragm, would also result in inappropriate binning, inaccurate tumor location, and noticeable imaging artifacts. 8 , 13 …”
Section: Introductionmentioning
confidence: 99%